HUBUNGAN ANTARA NEGATIVE AFFECT DENGAN MOTIVASI KERJA PADA KARYAWAN - Mabruroh, Afika Devi (EMPATHY Jurnal Fakultas Psikologi, 2013)
Â AbstractThis study aimed to determine the relationship between negative Affect the motivation to employees. The subjects were all employees of the opposite sex of men and women, at least one year working period, working in public hospitals. PKU Muhammadiyah Delanggu Klaten. The data was collected using the Negative Affect Scale and Work Motivation Scale. Data obtained from this study were analyzed using the techniques of the Pearson Product Moment Correlation and aided by computational systems with Statistical Software Program for Service Solution 19.0 for Windows (SPSS 19.0 for Windows). Based on the analysis it is known that the correlation coefficient between the two variables is rxy = -0.485 with p = 0.000 (p <0.01). Negative Affect Variables contributing 19% effective in reducing the motivation to work. Hypothesis is accepted that there is a negative relationship between negative Affect the motivation to employees. The conclusion of this study is that there is a very significant negative relationship between negative Affect the motivation to employees. The higher level of negative Affect Hospital employee owned. RSU. PKU Muhammadiyah Delanggu Klaten, the lower the motivation to work. Vice versa, the lower the negative Affect the higher levels of employee motivation RSU. PKU Muhammadiyah Delanggu Klaten. The majority of employees (75%) had negative Affect categorized as moderate and the majority of employees (55%) had a low work motivation. Keywords: Negative Affect, motivation, employee